Impact of illegal logging operation on Nigerian economy: A concise review (Agriculture, Food, and Natural Resources Journal, 2024)
Encroachment into forest estates and illegal timber logging activities in Nigeria have serious and negative effects on the country's economy, environment, forest soil, forest biodiversity, and rural communities. This study reviews concisely how illegal logging hurts Nigeria's GDP and suggests ways to tackle the problem. Illegal logging causes deforestation, loss of plant and animal species, soil erosion, water pollution, and contributes to climate change by releasing more carbon into the atmosphere. These environmental problems harm forests and make life harder for people who rely on them. In addition, illegal logging not only hinders everyone's ability to flourish but also exacerbates conflict, weakens the government, and breeds corruption. Hence, the need to strengthen and enforce the forest policy laws better, involve local communities in forest management, improve how forests are governed, promote sustainable logging practices, create new job opportunities in rural areas, work with other countries to stop illegal logging, and do more research to understand the problem better. By doing these things, Nigeria can reduce the damage caused by illegal logging, protect its environment, help communities thrive better, block loopholes, and improve income generation in the government treasury.
Keywords: Economy; Illegal logging; Timber; Utilization; Wood products